2003
DOI: 10.1016/s0378-1097(03)00178-2
|View full text |Cite
|
Sign up to set email alerts
|

The collagenase activity ofPorphyromonas gingivalisis due to Arg-gingipain

Abstract: Degradation of type I collagen by Porphyromonas gingivalis was monitored by fluorogenic, sodium dodecyl sulfate^polyacrylamide gel electrophoresis (SDS^PAGE), and growth assays. All three assays showed that inactivation of both the rgpA and rgpB genes was necessary to completely eliminate the capacity of P. gingivalis to cleave type I collagen. Leupeptin, an Arg-gingipain-specific protease inhibitor, almost completely inhibited collagen degradation by P. gingivalis cells whereas cathepsin B inhibitor II, a Lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 19 publications
2
34
1
4
Order By: Relevance
“…Collagen degradation by periodontopathogens may thus be involved in gingival tissue destruction. The collagenolytic activity of P. gingivalis has been attributed to various proteinases (21,27). In the present study, we showed that AC-PACs inhibited collagen degradation by P. gingivalis in a dose-dependent manner, suggesting that ACPACs may contribute to reducing the destructive process.…”
Section: Discussionsupporting
confidence: 62%
“…Collagen degradation by periodontopathogens may thus be involved in gingival tissue destruction. The collagenolytic activity of P. gingivalis has been attributed to various proteinases (21,27). In the present study, we showed that AC-PACs inhibited collagen degradation by P. gingivalis in a dose-dependent manner, suggesting that ACPACs may contribute to reducing the destructive process.…”
Section: Discussionsupporting
confidence: 62%
“…The diversity of these enzymes is mainly correlated with the phylogenetic relationship of the three bacteria as follows: Clostridium, such as Clostridium histolyticum [7] and Clostridium perfringens [8]; Vibrio, such as Vibrio alginolyticus [9] and Vibrio parahaemolyticus [10]; and Porphyromonas, such as Porphyromonas gingivalis [11] and Porphyromonas endodontalis [12]. These microbes are pathogens or conditional pathogenic bacteria which potentially produce toxin.…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes degrade collagens, constituents of extracellular matrix (ECM) found in vertebrate tissues, and contribute significantly to host tissue damage [18]. For instance, Arg gingipains, that are virulence factors produced by a periodontal pathogen P. gingivalis, possess collagenolytic activity [19]. Collagenase has been suggested as a putative virulence factor in F. columnare based on its absence in F. johnsoniae, a nonvirulent member of Flavobacteria, as revealed by suppressive subtractive hybridization analysis [35].…”
Section: Discussionmentioning
confidence: 99%